The Organization and Processing of Verbs and Nouns in the Mental Lexicon - Gopee Krishnan; Shivani Tiwari (Journal of All India Institute of Speech and Hearing)
The organizational as well as the processing differences between grammatical classes of words (e.g., verbs & nouns) have recently become a topic of interest among psycholinguists, researchers into language acquisition, and aphasiologists. Previous studies have shown that verbs, as a class, are more complex compared to nouns. Although this is the case, whether the difference between nouns and verbs lies at an organizational or processing level has not been thoroughly investigated. In this context, the objective of the current study was to probe into this issue by employing a semantic association judgment paradigm in a group of 25 normal subjects. The dependent variable (reaction time - RT) of nouns and verbs showed faster RT for the semantically associated pairs compared to the unassociated pairs, replicating previous similar results using nouns. Although, the verb pairs too showed such a tendency, the overall RT required for verbs was more than that for nouns. In addition, the analysis of the error data further revealed the complex interaction of the semantic attribute in nouns and verbs. Based on these findings, we argue that both nouns and verbs have similar organizational principle within the mental lexicon, yet with definite processing differences between the two, as indicated by the RT differences and error analysis.